Thyroid-related adverse events induced by immune checkpoint inhibitors - Chera, Alexandra; Stancu, Andreea Lucia; Bucur, Octavian (Frontiers in Endocrinology, 2022)
Immune checkpoint inhibitors, namely anti-CTLA-4, anti-PD-1 and anti-PD-L1 monoclonal antibodies, have emerged in the last decade as a novel form of cancer treatment, promoting increased survival in patients. As they tamper with the immune response in order to destroy malignant cells, a new type of adverse reactions has emerged, known as immune-related adverse events (irAEs), which frequently target the endocrine system, especially the thyroid and hypophysis. Thyroid irAEs include hyperthyroidism, thyrotoxicosis, hypothyroidism and a possibly life-threatening condition known as the “thyroid storm”. Early prediction of occurrence and detection of the thyroid irAEs should be a priority for the clinician, in order to avoid critical situations. Moreover, they are recently considered both a prognostic marker and a means of overseeing treatment response, since they indicate an efficient activation of the immune system. Therefore, a multidisciplinary approach including both oncologists and endocrinologists is recommended when immune checkpoint inhibitors are used in the clinic.